Understanding gender, marital status & education as internal migration factors in developing countries - Dibyo Waskito Guntoro; Setyabudi Indartono; Irmadatus Sholekhah (Universitas Negeri Malang, 2019)
This study aims to understand the factors of gender, marital status, and education in influencing the decision to carry out internal migration in developing countries, especially Indonesia between 2007-2015. This study uses secondary data in 2007 and 2015 from the Indonesian Family Life Survey (IFLS). After cleaning and adjusting data, a total of 4,642 respondents who met the requirements were used as research samples. The results showed that individual characteristics of sex and marital status had a significant effect on the tendency for internal migration in Indonesia. as well as education determines a person perform the migration. Further research requires a deeper review of social and economic factors.Penelitian ini bertujuan untuk memahami faktor gender, status perkawinan, dan pendidikan dalam mempengaruhi keputusan melakukan migrasi internal di negara berkembang, khususnya Indonesia antara tahun 2007-2015. Penelitian ini menggunakan data sekunder tahun 2007 dan 2015 dari Indonesian Family Life Survey (IFLS). Setelah dilakukan pembersihan dan penyesuaian data, sebanyak 4.642 responden yang memenuhi syarat dijadikan sebagai sampel penelitian. Hasil penelitian menunjukkan bahwa faktor karakteristik individu yang terdiri dari jenis kelamin dan status perkawinan berpengaruh signifikan terhadap kecenderungan melakukan migrasi internal di Indonesia. Begitu juga pendidikan menentukan seseorang melakukan migrasi. Penelitian selanjutnya diperlukan tinjauan lebih dalam mengenai faktor sosial dan ekonomi.DOI: http://dx.doi.org/10.17977/um017v24i22019p098